1997
DOI: 10.1021/jm970176k
|View full text |Cite
|
Sign up to set email alerts
|

N6-Cyclopentyl-3‘-substituted-xylofuranosyladenosines:  A New Class of Non-Xanthine Adenosine A1 Receptor Antagonists

Abstract: The present study explores the C-3' site of the 3-deoxy-3-xylofuranosyl ring of nucleoside analogues with an adenine or N6-cyclopentyladenine (CPA) base moiety and evaluates the effect on adenosine receptor affinity. Two series of sugar-modified adenosines, i.e., 3'-amido-3'-deoxyadenosines and 3'-amidated 3'-deoxyxylofuranosyladenines, were synthesized and tested for their affinity at A1 and A2a receptors in rat brain cortex and rat striatum, respectively. The modest affinity found in the "xylo series" prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…The proton signals of the dangling chain of La and 4a/6a are as easy to assign as their precursors 1aϪ3a, which will be reported elsewhere, with the triplet of (Table 1 and 2) to their precursors and other reported adenine analogues. [31] However, as revealed by a 1 H- 13 C heteronuclear correlation experiment, the 13 C signal of CH 2 NCH 2 PPh 2 is shifted to higher frequency between δ C ϭ 57.92 and 53.13 ppm and appears as a triplet or broad singlet due to coupling with the phosphorus atoms, while the signal of AdeCH 2 CH 2 remains as a singlet between δ C ϭ 42.58 and 41.69 ppm. The CH 2 PPh 2 signal, which appears as a doublet of doublets, doublet or broad singlet due to the 1 J P,C and/or 3 J P,C couplings, appears at the highest frequency in the alkyl region.…”
Section: Characterization Of La Lb and 1a/b؊6a/bmentioning
confidence: 95%
See 3 more Smart Citations
“…The proton signals of the dangling chain of La and 4a/6a are as easy to assign as their precursors 1aϪ3a, which will be reported elsewhere, with the triplet of (Table 1 and 2) to their precursors and other reported adenine analogues. [31] However, as revealed by a 1 H- 13 C heteronuclear correlation experiment, the 13 C signal of CH 2 NCH 2 PPh 2 is shifted to higher frequency between δ C ϭ 57.92 and 53.13 ppm and appears as a triplet or broad singlet due to coupling with the phosphorus atoms, while the signal of AdeCH 2 CH 2 remains as a singlet between δ C ϭ 42.58 and 41.69 ppm. The CH 2 PPh 2 signal, which appears as a doublet of doublets, doublet or broad singlet due to the 1 J P,C and/or 3 J P,C couplings, appears at the highest frequency in the alkyl region.…”
Section: Characterization Of La Lb and 1a/b؊6a/bmentioning
confidence: 95%
“…As shown by 31 P{ 1 H} NMR spectroscopy, however, there is always a trace of unidentified impurities (δ P ഠ 40.6, 37.7 and 36.5 ppm for sulfides; δ P ഠ 27.0 ppm for selenides) in the reaction mixture, implying that the PϪCϪN bond is not very robust under oxidation conditions. Attempts to get rid of the impurities were not successful by either chromatography or recrystallisation.…”
Section: Preparation and Oxidation Of La And Lbmentioning
confidence: 98%
See 2 more Smart Citations
“…In 1988, Lohse et al published the properties of N 6 -cyclohexyl-2',3'-dideoxyadenosine 52, and showed it to possess antagonistic properties [94]. More significantly, Van Calenberg et al demonstrated nm affinity with ribose-modified compounds [95]. Cyclopentyl adenosine (CPA) was altered at the 3'-position with various amide derivatives.…”
Section: The Adenosine a 1 Receptormentioning
confidence: 99%